Catalytic 2‑Ethylhexanoic Acid Promotes Mild Miyaura Borylations - Klootwyk, Brittany M.; Ruble, J. Craig; Cumming, Graham R.; Woerly, Eric M. (Journal of organic chemistry, 2024)
The Miyaura borylation of aryl and heteroaryl chlorides and bromides using a combination of potassium carbonate and 5 mol % 2-ethylhexanoic acid at 25 °C is reported. The in situ generation of a catalytic amount of potassium 2-ethylhexanoate under these conditions avoids the need for special handling of stoichiometric quantities of hygroscopic potassium 2-ethylhexanoate during the reaction setup as well as difficulties in removing the resulting carboxylic acid during product isolation.